Feasibility of community level interventions for pre-eclampsia: perspectives, knowledge and task-sharing from Nigeria, Mozambique, Pakistan and India - Kinney, Mary V. (2016)
Hypertensive disorders of pregnancy (HDP), particularly pre-eclampsia and eclampsia, remain one of the leading causes of maternal mortality and are contributory in many foetal/newborn deaths. This editorial discusses a supplement of seven papers which provide the results of the first round of the CLIP (Community Level Interventions for Pre-eclampsia) Feasibility Studies. These studies report a number of enablers and barriers in each setting, which have informed the implementation of a cluster-randomized trial (cRCT) aimed at reducing pre-eclampsia-related, and all-cause, maternal and perinatal mortality and major morbidity using community-based identification and treatment of pre-eclampsia in selected geographies of Nigeria, Mozambique, Pakistan and India. This supplement unpacks the diverse community perspectives on determinants of maternal health, variant health worker knowledge and routine management of HDP, and viability of task sharing for preeclampsia identification and management in select settings. These studies demonstrate the need for strategies to improve health worker knowledge and routine management of HDP and consideration of expanding the role of community health workers to reach the most remote women and families with health education and access to health services.